2017
DOI: 10.1155/2017/8069529
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases Polymorphisms as Prognostic Biomarkers in Malignant Pleural Mesothelioma

Abstract: Background Malignant pleural mesothelioma (MPM) is a rare disease with a relatively short overall survival (OS). Metalloproteinases (MMPs) have a vast biological effect on tumor progression, invasion, metastasis formation, and apoptosis. MMP expression was previously associated with survival in MPM. Our aim was to evaluate if genetic variability of MMP genes could also serve as a prognostic biomarker in MPM. Methods We genotyped 199 MPM patients for ten polymorphisms: rs243865, rs243849 and rs7201, in MMP2; rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
(38 reference statements)
0
16
0
Order By: Relevance
“… 6 In a previous paper we studied the possible role of single nucleotide polymorphisms (SNPs) as potential markers of treatment response. 7 We identified MMP9 rs2250889, MMP9 rs20544 , MMP14 rs1042703 as statistically significantly associated with overall survival (OS) in MM. Carriers of the polymorphic MMP9 rs2250889 and MMP14 rs1042703 alleles had shorter OS, compared to non-carriers, while carriers of polymorphic MMP9 rs20544 allele had longer OS.…”
Section: Introductionmentioning
confidence: 96%
“… 6 In a previous paper we studied the possible role of single nucleotide polymorphisms (SNPs) as potential markers of treatment response. 7 We identified MMP9 rs2250889, MMP9 rs20544 , MMP14 rs1042703 as statistically significantly associated with overall survival (OS) in MM. Carriers of the polymorphic MMP9 rs2250889 and MMP14 rs1042703 alleles had shorter OS, compared to non-carriers, while carriers of polymorphic MMP9 rs20544 allele had longer OS.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, a study including 199 Slovenian malignant mesothelioma patients suggested that MMP polymorphisms may have a role as prognostic biomarkers in malignant mesothelioma, as carriers of polymorphic MMP9 rs2250889 allele had shorter time to progression and shorter overall survival compared to noncarriers. In contrast, carriers of at least one polymorphic MMP9 rs20544 allele had longer time to progression and longer OS (overall survival than noncarriers [112].…”
Section: Genes Involved In Matrix Remodellingmentioning
confidence: 89%
“…Many studies have identified molecular pathways and mutations important in MPM, including BAP1; yet, there remains a paucity of biomarkers that are currently in the clinical setting . Susceptibility and prognostic markers may allow personalized screening, detection, and treatment approaches, which have been a challenge for MPM that is typically diagnosed in its later stage.…”
Section: Discussionmentioning
confidence: 99%